Counseling as a Smoking Behavior Service Strategy for Students at SMA Negeri 4 Jeneponto - Fatmawati M Saing; Elna Sari; Rasniah Sarumi; Endang Sri Mulyawati L; Dewi Rahmawati (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Smoking in adolescence has a long-term impact on physical health as well as social and psychological development. This study aims to analyze the effectiveness of group counseling services in reducing smoking behavior among SMA Negeri 4 Jeneponto students. The study used a quasi-experimental design with a quantitative approach, involving two groups: the intervention group that received Group Counseling (KKp) services and the control group that received Group Counseling (BKp) services. A total of 40 smoking students were selected through purposive sampling techniques. The instrument in the form of a structured questionnaire that measures the knowledge, attitudes, and actions of smoking, has been tested for validity and reliability. Data was collected through pre-test and post-test, as well as documentation of the counseling process. The normality test showed abnormal data distribution, so the analysis was carried out using the Wilcoxon and Mann-Whitney tests. Results showed significant improvements in student knowledge, attitudes, and actions in the intervention group (p < 0.05), while the control group showed no significant changes. The average post-test scores of the intervention group were higher, and more respondents achieved the “good” category in all three domains. The conclusion of this study is that group counseling is effective in reducing smoking behavior among high school students, especially at SMA Negeri 4 Jeneponto.